Pooled-analysis of tadalafil and tamsulosin for ureteral calculi - Sun, Fengze; Liu, Hongquan; Wu, Gang; Liu, Ming; Liu, Shangjing; Wang, Lin; Zou, Qingsong; Cui, Yuanshan; Wu, Jitao (Frontiers in Pharmacology, 2024)
Objective Urolithiasis is a common urological diseases and affects the daily life of patients. Medical expulsive therapy has become acceptable for many parents. We conducted a meta-analysis to determine the efficacy and safety of tadalafil compared with tamsulosin for treating distal ureteral stones less than 10 mm in length. Methods Related studies were identified via searches of the PubMed, Embase, and Cochrane Library databases. All the articles that described the use of tadalafil and tamsulosin for treating distal ureteral stones were collected. Results A total of 14 studies were included in our meta-analysis. Our results revealed that tadalafil enhanced expulsion rate [odds ratio (OR) = 0.68, 95% confidence interval (CI): 0.47 to 0.98, p = 0.04]; reduced expulsion time [mean difference (MD) = 1.22, 95% CI (0.13, 2.30), p = 0.03]; lowered analgesia use [MD = 38.66, 95% CI (7.56, 69.77), p = 0.01] and hospital visits [MD = 0.14, 95% CI (0.06, 0.22), p = 0.0006]. According to our subgroup analysis, either tadalafil 5 mg or 10 mg did not promote expulsion rate and accelerate expulsion time compared with tamsulosin. But patients receiving 5 mg tadalafil decreased analgesia usage [MD = 101.04, 95% CI (67.56, 134.01), p < 0.00001]. Conclusion Compared with tamsulosin, tadalafil demonstrates a higher expulsion rate and less expulsion time for patients with distal ureteral stones less than 10 mm with a favorable safety profile.